Subsurface nitrate reduction under wetlands takes place in narrow superficial zones. Issue 21 (2nd November 2017) - Ribas, D.; Calderer, M.; Marti, V.; Johnsen, A. R.; Aamand, J.; Nilsson, B.; Jensen, J. K.; Engesgaard, P.; Morici, C.
ABSTRACT: This study aims to investigate the depth distribution of the Nitrate Reduction Potential (NRP) on a natural and a re-established wetland. The obtained NRP provides a valuable data of the driving factors affecting denitrification, the Dissimilatory Nitrate Reduction to Ammonium (DNRA) process and the performance of a re-established wetland. Intact soil cores were collected and divided in slices for the determination of Organic Matter (OM) through Loss of Ignition (LOI) as well as Dissolved Organic Carbon (DOC) and NRP spiking nitrate in batch tests. The Nitrate Reduction (NR) was fitted as a pseudo-first order rate constant (k) from where NRPs were obtained. NR took place in a narrow superficial zone showing a dropping natural logarithmic trend along depth. The main driving factor of denitrification, besides depth, was OM. Although, DOC and LOI could not express by themselves and absolute correlation with NRP, high amounts of DOC ensured enough quantity and quality of labile OM for NR. Besides, high concentration of LOI but a scarce abundance of DOC failed to drive NR. DNRA was only important in superficial samples with high contents of OM. Lastly, the high NRP of the re-established wetland confirms that wetlands can be restored satisfactorily.